Answer:
(f - g)(2) = 2
Step-by-step explanation:
Given the functions below, find (f - g) (2).
f(x) = x² + 3
g(x) = 4x – 3
(f - g)(x) = (x²+3)-(4x-3)
(f - g)(x) = x²+3-4x+3
(f - g)(x) = x²-4x+6
(f - g)(2) = (2)²-4(2)+6
(f - g)(2) = 4-8+6
(f - g)(2) = 2
Answer:
Step-by-step explanation:
In propositional logic and Boolean algebra, De Morgan's laws are a pair of transformation rules that are both valid rules of inference. ... The rules allow the expression of conjunctions and disjunctions purely in terms of each other via negation.
Answer:
just write the numbers of coins a different way
Answer:
its number 3
Step-by-step explanation: